El e-commerce y la satisfacción del cliente del e-marketplace linio en el comercio internacional en el distrito de Iquitos 2023 - Arevalo Documet, Norusca Frida (2023)
The objective of the research was to determine the relationship between e commerce and customer satisfaction of the Linio e-marketplace in international trade in the district of Iquitos - 2023, where an applied type study was used, correlational descriptive level and non-experimental design. taking as a population 100 volunteers who live in the district of Iquitos and have purchased through the Linio e-marketplace, to whom a questionnaire was applied to collect information. According to the results, E-Commerce achieved a regular rating (28%) because the website sometimes took time to load between actions and their responses, sometimes the products were correct, the website was accurate in terms of products, sometimes had customer service representatives available online, and sometimes had strong security measures in place to protect user information. For its part, with 29% satisfaction, the service provided by the online store ranges from good to excellent. She is always interested in the well-being of the customers, but there are times when she offers superior quality and also contributes to the increase in purchases through this platform. Finally, it was determined that there is a positive and significant relationship between the variables, contrasted by a correlation of 0.862 and a sig. at the 0.000 level.